Status of Astronomy at Mbarara University of Science and Technology - Anguma, Simon; Jurua, Edward (Proceedings of the International Astronomical Union, 2009)
In this paper, we describe the role astronomy has played in interesting students towards taking physics as a major subject during their final year in Mbarara University of Science and Technology (MUST). This has resulted into some former students from MUST taking up postgraduate studies in Astrophysics and Space Science in South African Universities. The plans to strengthen and develop Astronomy in Uganda are also discussed, and in particular, the strategies for organizing the IYA2009 are outlined.
The Role of Astronomy in Society and Culture Proceedings IAU Symposium
Keywords: Keyword1; Keyword2; Keyword3